The Relationship Between Lava Fountaining and Vent Morphology for the 2014–2015 Holuhraun Eruption, Iceland, Analyzed by Video Monitoring and Topographic Mapping - Witt, Tanja; Walter, Thomas R.; Müller, Daniel; Guðmundsson, Magnús T.; Schöpa, Anne (Frontiers in Earth Science, 2018)
Fissure eruptions are associated with lava fountains which often show complex distinct venting activity in pulsating form, and the development of characteristic morphological features such as scoria or spatter cones. Most morphological studies are based on observations of old structures and are not related to direct observations and systematic records of vent activity. The 2014–2015 Holuhraun eruption site, Iceland, offered an exceptional opportunity to study the location and evolution of these cones and their relationship to venting dynamics in unprecedented detail. Here we analyze records from lava fountain activity at distinguished vents, captured during the 2014–2015 Holuhraun eruption, and compare them with the morphology of spatter cones that developed. We conducted a fieldwork mapping project combining terrestrial laser scanning (TLS) and unmanned aerial vehicle (UAV) aerophoto techniques to characterize the cone morphologies. We recorded videos of the eruption and used edge detection and particle image velocimetry to estimate venting heights and particle velocities. We find that the number of active vents producing lava fountains decreases from 57 along the whole line of fire to 10 lava fountains at distinct vents during the first 5 days of the eruption. We suggest that this happens by channeling the magma supply in the subsurface developing conduits. Thereby we see that at the locations where spatter cone morphology developed, the strongest and the highest lava fountains with high ejection velocities were recorded on the very first days of the eruption. In addition, the sites that eventually developed moderate or weak cone morphologies were identified as less active lava fountain locations during the early stage of the eruption. The comparison of our topographic datasets shows that the spatter cones remained similar in shape but increased in size as the eruption progressed. In addition, we suggest that the observed changes in morphology may have affected lava ponding in the crater, which in turn strongly influenced the lava fountain heights. Our results improve the general understanding of landscape evolution in rift zones and demonstrate the close relationship between cone morphology and lava fountain activity at the onset of an eruption.